Ways to improve the safety of operators of self-propelled vehicles - Belova T.I.; Sukhov S.S.; Konchits S.V.; Filippov A.A. (Научно-технический вестник Брянского государственного университета)
In order to manage the safety of work of operators of self-propelled transport machines (STM) proposed a security model of STM in the form of a two-unit probabilistic model, which allows for semi-optimum parameters of the speed limit and to increase the reliability of protection of workers through the use of the proposed technical device.